Identification of endophytic actinomycetes isolated from hopea ferrea and its antibacterial activity against cariogenic bacterium - Nur Raihan Aqilah Mohammad Azmin,; Nurul ‘Izzah Mohd Sarmin,; Hasnah Begum Said Gulam Khan,; Mukarramah Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dental caries affects around 36% of the world's population and results in the loss of primary teeth in about 530 million youngsters. It is described as the loss of the enamel layer of the tooth by acids generated by the activity of cariogenic bacterium such as Streptococcus mutans on carbohydrates. This study aims to identify bioactive endophytic actinomycetes as an antibacterial agent against S. mutans DSM 20523 and to identify the bioactive endophytic actinomycetes using the 16S rRNA sequencing approach. To determine the percentage zone of inhibition, three endophytes at 10-day-old culture have been streaked onto ISP2. Then, S. mutans was streaked perpendicular to the endophytes. Crude extracts from three endophytes have been prepared by using four different types of media namely Tryptic Soy broth, Kings B, International Streptomyces Project Medium No.1 (ISP1) and Starch Casein broth. These crude extracts proceeded to undergo disk diffusion and MIC assays against S. mutans. All three endophytes from streaked plates with the highest percentage zone of inhibition were identified using the 16S rRNA gene molecular approach for characterisation. Endophytic actinomycetes which were isolated from Hopea ferrea showed potent antibacterial activity against S. mutans. All endophytic actinomycetes isolates from streak plates showed good inhibitory activity against the S. mutans. The highest percentage of inhibition was shown by the PT9-13S2 isolate followed by PT9-8S2 and PT9-13W2. Furthermore, crude extracts of PT9-8S2 and PT9-13W2 (the highest ZOI) from TSB media showed inhibitory activities against S. mutans, from disk diffusion as well as minimum inhibitory assays. From the 16S rRNA molecular approach, endophytic actinomycetes PT9-8S2 was closely related to Streptomyces collinus while PT9-13S2 and PT9-13W2 were closely related to Streptomyces malachitospinus. From this study, endophytic actinomycetes showed a promising source as antibacterial agents against cariogenic bacterium S. mutans which is the main causative agent of dental caries.